2006
DOI: 10.1177/1094670505278867
|View full text |Cite
|
Sign up to set email alerts
|

Measuring Service Quality in E-Retailing

Abstract: To managers of companies with a Web presence, an awareness of how customers perceive service quality is essential to understanding what customers value in an online service transaction. Previous research in e-service quality has primarily focused on the interaction of the consumer and the Web site while missing the big picture that e-service quality is composed of more than Web site interactivity. The goal of this article is to extend the work on e-service quality to encompass not only Web site interactivity o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

32
689
1
53

Year Published

2007
2007
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 832 publications
(858 citation statements)
references
References 43 publications
32
689
1
53
Order By: Relevance
“…Confirmability was also ensured by mapping the existing literature that described similar results to the research of customer e-service adoption [2,3,64,65].…”
Section: Confirmabilitymentioning
confidence: 97%
See 3 more Smart Citations
“…Confirmability was also ensured by mapping the existing literature that described similar results to the research of customer e-service adoption [2,3,64,65].…”
Section: Confirmabilitymentioning
confidence: 97%
“…Collier and Bienstock [64] studied the importance of customer satisfaction in e-Retailing. The results showed that the customer's perception of e-services determines whether a customer will return to a particular e-service.…”
Section: Discussion Of Findingsmentioning
confidence: 99%
See 2 more Smart Citations
“…In this study, e-loyalty is defined as perceived loyalty of customers towards websites and their intention to visit the same website on their second purchase. There are various complex drivers of e-loyalty according to Choi, S. I. Kim, and S. H. Kim (2010), Collier and Bienstock (2006), Deb andChavali (2009), andPonirin, Scott, andVon Der Heidt (2009). Therefore, for the purpose of this study, authors adopt three dimensions to examine customer e-loyalty: word-of-mouth, complaining behavior, and future purchase intention.…”
Section: Literature Review E-loyaltymentioning
confidence: 99%